Pedagogy: Teaching Practices of American Colonial Educators in the Philippines - Martin, Isabel Pefianco (Archīum Ateneo, 2024)
Filipino historian and essayist Renato Constantino wrote: “With American education, the Filipinos were not only learning a new language; they were not only forgetting their own language; they were starting to become a new type of American.” What specific strategies did the American colonizers use to create this new type of American? How did they use the public schools to produce their cultural clones? The answer may be found in the language and literature teaching practices of American colonial educators in the Philippines. This paper argues that the Anglo American canon of literature imposed on the Filipinos would not have been as potent without its powerful partner: colonial pedagogy.